Patient Safety Culture in Community Pharmacies Serving the Indonesian Chronic Disease Referral Programme (BPJS Program Rujuk Balik): A Sequential Exploratory Mixed-Methods Study - Eka Pebi Hartianty; Hesty Utami Ramadaniati; Antonius Adji Prayitno Setiadi; Sahat Saragi (Community Medicine and Education Journal, 2026)
Community pharmacies are the most accessible health facility in Indonesia and a central interface of the BPJS Kesehatan Program Rujuk Balik (PRB) for chronic disease pharmaceutical care, yet empirical evidence on patient safety culture in this setting remains sparse. This sequential exploratory mixed-methods study characterised the twelve-dimension patient safety culture profile, quantified the cognition-to-practice gap, and identified actionable system priorities. Three sequential phases were conducted between July 2024 and February 2025: a cross-sectional Community Pharmacy Survey on Patient Safety Culture (CPSOPSC) among 35 pharmacy staff (Cronbach’s α=0.84), an expanded indicator survey of 43 staff, and semi-structured interviews with three pharmacists practising in PRB-contracted pharmacies. Highest positive responses occurred on teamwork (97.1%, 95% CI 95.0–99.2), organisational learning (87.6%, 95% CI 84.0–91.2), physical space (84.8%, 95% CI 80.9–88.7) and staff training (84.3%, 95% CI 80.5–88.1); lowest on documentation of errors (23.8%, 95% CI 19.3–28.3), staffing and workload (52.1%, 95% CI 47.0–57.2) and patient counselling (54.3%, 95% CI 49.2–59.4). Firth-penalised logistic regression with cluster-robust variance (area under the receiver-operating-characteristic curve [AUC]=0.78, 95% CI 0.71–0.85) identified prescription volume (adjusted odds ratio [aOR] 3.12, 95% CI 1.78–5.47, p=0.001) and independent ownership (aOR 2.41, 95% CI 1.32–4.40, p=0.004) as dominant correlates of low-documentation outcome. The expectation–experience indicator gap was 21.2 percentage points (95% CI 17.4–25.0, p<0.001, Cohen’s d=1.42). Eight qualitative themes triangulated with quantitative dimensions confirmed documentation infrastructure, workforce capacity, and counselling time as priority structural levers. Findings support extending BPJS PRB credentialing to include patient-safety indicators, advancing Sustainable Development Goals 3.8, 3.d, 4.4, 10.3 and 17.18.